Laboring to Play : Home Entertainment and the Spectacle of Middle-Class Cultural Life, 1850-1920 - Dawson, Melanie, 1967- (Book collections on Project MUSE., 2005)
"Drawing from 19th- and early-20th-century fiction, guidebooks on leisure, periodicals and newspaper columns, and a polemical examination of class structures, this book interrogates the ways that leisure performances (such as parlor games, charades, home dramas, and tableaux vivants) encouraged participants to test out the boundaries that were beginning to define middle-class lifestyles."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved